A model-based approach to combine conformance and load tests: an eHealth case study. (2018) - Krichen, Moez; Maâlej, Afef Jmal; Lahami, Mariam
In this paper, we propose a new model-based framework that combines both conformance and load tests in the context of real-time systems. Our new framework is based on the model of extended timed automata with inputs/outputs and shared integer variables. In addition, we define a new extended timed input output conformance relation etioco. This latter allows to compare a given implementation with respect to its specifications considering load conditions. We also discuss some modelling issues and we provide a new technique for deriving analogue-clock tests from the specification of the system under test (SUT). In order to show the relevance of our approach, we report on a critical case study from the healthcare field. An important contribution in this work was to use a rich formalism to model multi-user systems and to combine conformance and load tests in the same model. This point constitutes an important testing area that is usually misunderstood.